Age Is a Risk Factor for Gastroscopy-Assisted Capsule Endoscopy in Children - Wang, Hongli; Xie, Jing; Ren, Lu; Xiong, Liya; Xu, Wanfu; Gong, Sitang; Geng, Lanlan; Chen, Peiyu (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The aim of this study was to explore the risk factors for the incidence of gastroscopy assisted capsule endoscopy and the small bowel transit time in pediatric patients who underwent capsule endoscopy examination. Materials and Methods: A retrospective analysis was performed to analyze the clinical data collected from pediatric patients who underwent capsule endoscopy examination. Results: A total of 239 pediatric patients were enrolled in this study. About 196 (82.0%) patients completed the entire small bowel capsule endoscopy examination, while 3 (1.3%) patients were subjected to capsule retention. Only age, not gender, height, body weight, body mass index, chief complaint, and intestinal preparation medications, has been identified as a risk factor for the incidence of gas troscopy-assisted capsule endoscopy (P < .05) by multivariate logistic regression. Further analysis showed that the small bowel transit time in the self-swallowed group was shorter than that in the gastroscopy-assisted group, while no significant difference was obtained in other factors, including intestinal preparation medications, metoclopramide, and lesions in the small intestine, which did not signifi cantly affect small bowel transit time compared with the corresponding control group (P > .05). Conclusion: A comprehensive assessment is required before performing capsule endoscopy, because age has been identified as a critical risk factor for the incidence of gastroscopy-assisted capsule endoscopy in pediatric patients. Cite this article as: Wang H, Xie J, Ren L, et al. Age is a risk factor for gastroscopy-assisted capsule endoscopy in children. Turk J Gastroenterol. 2024;35(1):41-47.